Gender differences in biometry prediction error and intra‐ocular lens power calculation formula. (15th June 2014) - Behndig, Anders; Montan, Per; Lundström, Mats; Zetterström, Charlotta; Kugelberg, Maria
Abstract Purpose To analyze changes over time in biometry prediction error (BPE) after cataract surgery with special reference to the impact of gender and the intra‐ocular lens (IOL) calculation formula. Methods About 65% of Swedish cataract surgery units participating in the outcome registration of the National Cataract Register (NCR) were included in this prospective register study. Data for planned and postoperative refraction and keratometry during the month of March 2004–2013 were analyzed, divided by gender. The newly introduced variables axial length and IOL calculation formula were analyzed for March 2013. Gender differences in BPE with correct sign (BPESign) and absolute biometry prediction error (BPEAbs) were compared for the Haigis' and Sanders‐Retzlaff‐Kraff T (SRK/T) formulas. Results The BPEAbs decreased throughout the study period. In 2004–2006, the BPEAbs was larger in women than in men (p < 0.05), but this difference disappeared from 2007. For 2004 through 2009, the mean BPESign was −0.105 ± 0.79D for women, but −0.003 ± 0.73D for men. After 2009, this myopic error for women gradually diminished. The Haigis' formula performed better in women than the SRK/T formula (p < 0.001); the SRK/T formula rendered a BPESign similar to that from 2004 to 2009 in women. Women had steeper corneas and shorter axial lengths than men (p < 0.001). Conclusion The myopic BPE in women – associated with steeper corneas and shorter axial lengths – is decreasing, possibly owing to an increased use of the Haigis' formula. Using the Haigis' formula to a higher extent can potentially further reduce the BPEs after cataract surgery.